Reading and the Development of Social Understanding: Implications for the Literacy Classroom. (19th September 2018) - Kozak, Stephanie; Recchia, Holly
Abstract: Research has underscored the cognitive benefits of reading, but scholars have also begun to explore its implications in the socioemotional domain. The authors review research exploring the links between reading and social understanding skills such as empathy and perspective taking, examine the qualities of literature that are posited to foster social understanding, and propose explanations of why reading may confer these benefits. Building on this review, the authors include ideas on how to incorporate this research into literacy classrooms by providing specific book suggestions and accompanying activities that may leverage the potential sociocognitive benefits of reading within a classroom context.